Imprisonment as a Criminal Sanction against Corporations in Forestry Crimes: How Is It Possible? - Hafrida Hafrida; Retno Kusniati; Yulia Monita (Hasanuddin Law Review, 2022)
Environmental harms are frequently part and parcel of ordinary commercial practice. This study aimed to highlight the importance of applying imprisonment as a corporate criminal sanction in forestry crimes to observe and consider individual and far-reaching victims. Forest crimes impact the community’s socio-cultural life and cause environmental damage by increasing global warming. Based on the laws and regulations, fines as criminal sanctions do not effectively deter corporations. Subsequently, imprisonment could be an alternative criminal sanction against corporations through identification where corporate liability could be identified through its management. Actions taken by the management are not based on their rights and authorities but those of the corporations. Therefore, imprisonment and other sanctions such as restitution are expected to effectively and viably address forestry crimes.